Guidelines for the measurement of BCR-ABL1 transcripts in chronic myeloid leukaemia. - Foroni, L; Wilson, G; Gerrard, G; Mason, J; Grimwade, D; White, H; de Castro, D; Austin, S; Awan, A; Burt, E; Clench, T; Farruggia, J; et al. (2011)
Molecular testing for the BCR-ABL1 fusion gene by real time quantitative polymerase chain reaction (RT-qPCR) is the most sensitive routine approach for monitoring the response to therapy of patients with chronic myeloid leukaemia. In the context of tyrosine kinase inhibitor (TKI) therapy, the technique is most appropriate for patients who have achieved complete cytogenetic remission and can be used to define specific therapeutic milestones. To achieve this effectively, standardization of the laboratory procedures and the interpretation of results are essential. We present here consensus best practice guidelines for RT-qPCR testing, data interpretation and reporting that have been drawn up and agreed by a consortium of 21 testing laboratories in the United Kingdom and Ireland in accordance with the procedures of the UK Clinical Molecular Genetics Society.